(untitled) (Italian Journal of Public Health, 2007)
Serotype Infantis ranks within the top-five Salmonella serotypes in many European countries. An association between this serotype and the poultry ecosystem is apparent in some geographic areas and could account for its persistent or emergent role as causative agent of human salmonellosis. Recently, in southern Italy isolation from eggs and poultry has become increasingly frequent, and in one case the egg yolk also cultured positive. Molecular typing was performed to assess the possible relationship among isolates from human, food and animal sources. Isolates of serotype Infantis identified in southern Italy between 2000 and 2005 rom various sources were submitted to pulsed field gel electrophoresis (PFGE) by a CHEF-Mapper apparatus fter endonuclease digestion of DNA by XbaI. PFGE patterns of isolates from swine and poultry reservoirs showed distinctive PFGE profiles and human solates shared pulsotypes with isolates from both sources. Moreover, egg isolates from different farms ppeared very similar to each other. Epidemiological investigation and risk assessment can obtain reliable and useful pointers from he pplication of molecular epidemiology techniques.